Penerapan Model Example Non Example Terhadap Peningkatan Kemampuan Pemahaman Konsep Peserta Didik Dalam Mata Pelajaran IPA - Intan Nurlatifah (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2019)
The problem in this research is the low comprehension of the concept in the subject of Science Lesson, the purpose of this research is to describe the learning process by applying the model of example non example on natural science subjects and to describe the enhancement of learner’s conceptual comprehension skills by applying the model of example non example on natural science subjects. Type of research which is classroom action research (PTK) as much as 2 cycle. This research is conducted by issuing data in the form of the results of the ability of understanding comprehension of science subjects, observation results, field notes and documentation results. Data analysis techniques that are quantitative and qualitative. Participants in this study were Va class learners as many as 39 people consisting of 19 men and 20 women. The results showed an increase in understanding of the concept of learners. In cycle I experienced an increase from the results of the category of low mastery in pre cycle into the category of medium mastery, in cycle II increased from the results of the category of medium mastery in cycle I into the category of very high mastery.